The Great Scorpene Leak: Prospects for India’s Submarine Programmes - Bana, Sarosh (2016)
India’s submarine construction programme has been jeopardised by a major data leak of its French-designed Scorpene submarines. The future of its new generation submarines under the Project 75 (India) contract has also been thrown into doubt.